Pelatiahan Pelaporan SPT Tahunan Wajib Pajak Orang Pribadi Melalui E-Filing - Harefa, Meilinda Stefani; Lumban Gaol, Vebry M.; Waruwu, Frans Jessens; Enjel Verawati (LPPM Universitas HKBP Nommensen, 2024)
The purpose of this community service is to provide direct training to residents/communities in Pangururan, Siallagan Village, and Ulos Village of Samosir Regency on filling out the 1770SS tax return through e-filing. This training was held at the Samosir Regency DEKRANASDA Hall on Saturday, 04 March 2023, starting at 09.00 until completion and was attended by 32 participants. This activity began with an opening prayer, opening activities by the Dinas Koperasi & UMKM Kabupaten Samosir, remarks from the head of the Faculty of Economics and Business, HKBP Nommensen University, presentation of material and practice with the Participatory Learning and Action (PLA) approach, discussion and closing. This training is very helpful for participants to report their taxes on time and avoid calculation errors. Technically, there were still obstacles during this training because the internet network was less supportive and participants did not master the use of laptops / smart phones as a medium in reporting taxes through e-filing. Nevertheless, over all the participants were very enthusiastic in responding to the explanation from the resource person and based on the explanation gradually the participants were able to report their taxes through e-filing.